(untitled) (Research, Society and Development, 2022)
This article addresses the theme of personalized education in the teaching of Geography and the importance of the integral formation of students, in values ​​and virtues, especially in basic education. This teaching-learning proposal goes against the massive, fragmented and alienating teaching of our days, which do not encourage students to concrete learning and the full development of their own potential. In this sense, this work presents the personalization of teaching as an alternative to promote the cultivation of intelligence and the total formation of the being, in response to the current educational crisis in Brazil. In order to do so, a bibliographic research was used in books, periodicals and national documents and a qualitative analysis of the information obtained. In this way, it was concluded that personalized education, in the teaching of Geography, is a possibility that must be further developed and practiced, since it is capable of carrying out the purpose of education: to lead students to effective learning and updating. of the powers of your personality.